PENGARUH LITERASI KEUANGAN SYARIAH, PERSEPSI RETURN, DAN MOTIVASI TERHADAP MINAT INVESTASI DI PASAR MODAL SYARIAH - Vania Evanita Puspitasari (2021)
This study aims to determine the effect of Islamic financial literacy, perceived return, and motivation on investment interest in the Islamic capital market. The research method is quantitative with a sample of 150 people living in Jabodetabek who know about the Islamic capital market. Collecting data using an online questionnaire via google form. Data were analyzed by multiple linear regression method using SPSS version 25 software data processing tool. Hypothesis testing using T test, F test, and coefficient of determination test. The results showed that the variables of Islamic financial literacy, perceived return, and motivation had a simultaneous effect on investment interest. Partially, the perceived return and motivation variables show a positive and significant effect, while the Islamic financial literacy variable has no effect on investment interest. From the results of the coefficient of determination test, it shows that the three independent variables affect the investment interest variable by 22%, the rest is influenced by other independent variables not examined. Based on the overall findings in this study, it is necessary to have a strategy in optimizing socialization and education related to the Islamic capital market so that it is more evenly distributed.